2023
DOI: 10.3390/ijms24032074
|View full text |Cite
|
Sign up to set email alerts
|

Trimethylamine N-Oxide Response to a Mixed Macronutrient Tolerance Test in a Cohort of Healthy United States Adults

Abstract: Plasma trimethylamine n-oxide (TMAO) concentration increases in responses to feeding TMAO, choline, phosphatidylcholine, L-carnitine, and betaine but it is unknown whether concentrations change following a mixed macronutrient tolerance test (MMTT) with limited amounts of TMAO precursors. In this proof-of-concept study, we provided healthy female and male adults (n = 97) ranging in age (18–65 years) and BMI (18–44 kg/m2) a MMTT (60% fat, 25% sucrose; 42% of a standard 2,000 kilo calorie diet) and recorded their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…A limitation of this line of research is that we do not have a clear consensus on how the underlying gut microbiome composition of a given group of individuals and the subsequent remodeling of the gut microbiota with long-chain n-3 PUFAs will impact physiological outcomes. As discussed below, an understanding of the microbiome integrated with other known variables of heterogeneity in the response to EPA and DHA will be critical in driving precision studies, as revealed in other disciplines relying on similar approaches [15][16][17].…”
Section: Gut Microbiomementioning
confidence: 99%
“…A limitation of this line of research is that we do not have a clear consensus on how the underlying gut microbiome composition of a given group of individuals and the subsequent remodeling of the gut microbiota with long-chain n-3 PUFAs will impact physiological outcomes. As discussed below, an understanding of the microbiome integrated with other known variables of heterogeneity in the response to EPA and DHA will be critical in driving precision studies, as revealed in other disciplines relying on similar approaches [15][16][17].…”
Section: Gut Microbiomementioning
confidence: 99%